Risk factors for invasive fungal infection in 5‐azacytidine treated patients with acute myeloid leukemia and myelodysplastic syndrome. (27th May 2021) - Tey, Amanda; Shaw, Briony; Cardamone, Luke; Shepherd, Sam; Paul, Eldho; Rogers, Ben; Shortt, Jake
Abstract: The rate of invasive fungal infection (IFI) in patients with myelodysplasia (MDS) and acute myeloid leukemia (AML) receiving 5‐azacytidine is incompletely defined and published recommendations for mold‐active fungal prophylaxis in such patients vary according to source. We performed a retrospective cohort study in order to identify contemporary IFI rates and infection‐related mortality in relation to known risk factors and the use of antifungal prophylaxis. One hundred and seventeen patients receiving 5‐azacytidine for MDS and low blast count AML were identified, of whom 71 (61%) received antifungal prophylaxis. The IFI rate was 7.7% across the entire cohort: 5.6% in those receiving prophylaxis vs 10.9% in the subgroup who did not ( P = .30). The presence of neutropenia at three months of treatment was associated with increased IFI risk (hazard ratio [HR] 8.29; (95% confidence interval [CI)] 1.61‐42.6; P = .01), and on multivariate analysis, IFI was independently associated with increased all‐cause mortality risk (HR 8.37; 95% CI 3.67 ‐ 19.11; P < .0001). These data further highlight the risk of IFI in this population and support the use of mold‐active prophylaxis in neutropenic patients receiving 5‐azacytidine for MDS and AML. Abstract : Hypomethylating agents such as 5‐azacytidine (AZA) are the mainstay of therapy for myelodysplasia (MDS) and acute myeloid leukemia (AML) in patients who are unfit for intensive treatment. Such patients are at risk of invasive fungal infection (IFI) complicating bone marrow failure and therapy‐induced cytopenias. Rates of IFI and recommendations for mold‐spectrum antifungal prophylaxis vary in the literature. We report "real world" experience in 117 AZA‐treated patients and demonstrate that the risk of IFI remains significant in this cohort and that IFI has high mortality rates. This data further support the use of mold‐spectrum prophylaxis in AZA‐treated MDS and AML patients.